Introduction to the Special Issue: Interventions to Reduce Challenging Behavior Among Individuals With Autism Spectrum Disorder. Issue 3 (May 2018) - Davis, Tonya N.; Rispoli, Mandy
The prevalence of autism spectrum disorder (ASD) is on the rise. In addition to the social communication skill deficits and restrictive repetitive behaviors and interests, many individuals with ASD engage in challenging behavior. Challenging behavior is associated with a multitude of negative outcomes. Challenging behavior may cause harm to the individual with ASD as well as limit opportunities for educational, vocational, and social participation and development. In addition, caregivers experience high stress and low quality of mental health. As a result, challenging behavior warrants intervention that is specifically tailored to the unique characteristics of individuals with ASD. The purpose of this Special Issue is to showcase recent research in the treatment of challenging behavior for individuals with ASD. This two-part Special Issue contains 12 studies that range from systematic and quality reviews of the intervention literature, to innovative treatment approaches, to studies that develop and evaluate treatments for restrictive and repetitive behaviors and interests.